Daya Tarik Objek Wisata Tujuh Semeja Dalam Meningkatkan Jumlah Pengunjung - Indah Kharisma Laras; Tenerman Tenerman (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2022)
The title of this research is about the Attraction of Tujuh Semeja Tourism Objects in Increasing the Number of Visitors. This study uses a qualitative method with purposive sampling technique and data collection techniques are observation, interviews and documentation. Data analysis techniques in this study used qualitative data analysis techniques, namely reducing data, presenting data and drawing conclusions. The results of this study indicate that the existence of marketing strategy communication is a strategy in increasing the number of visitors in the Tujuh Semeja tour. The market strategy used in attracting visitors to the Tujuh Semeja tour is product, place, promotion and price. Things that tourism managers do in implementing this marketing strategy are by creating signature coffee with various flavor variants, innovating development in stages, being active in promoting tourism through social media and setting prices according to the quality of coffee sold and adjusting visitors to middle class prices.